PENGUATAN KEPASTIAN HUKUM MELALUI ADMINISTRASI PERCERAIAN YANG BERORIENTASI PADA MASLAHAH: STRENGTHENING LEGAL CERTAINTY THROUGH DIVORCE ADMINISTRATION ORIENTED TO MASHLAHAH - Arindia, Michelle Pradnya; Maheswari, Auliya Kirana; Simamora, Nathania Tesamonika; Baidhowi, Baidhowi (Cahaya Ilmu Bangsa, 2025)
This article examines how legal certainty in Indonesia’s divorce administration can be strengthened through a maslahah-oriented approach that aligns Islamic jurisprudence with national law. Using a normative juridical method and literature analysis, the study explores the role of maqasid al-shari‘ah, especially the dharuriyyat al-khams, in guiding administrative practices that protect post-divorce rights. The findings show that applying maslahah supports fair arrangements in matters such as asset division, child custody, and financial obligations, while addressing recurring issues like procedural complexity and gaps between judicial rulings and civil registry processes. The study argues that reforms are including simplified procedures, stronger institutional coordination, digitalization of records, and consistent enforcement of court decisions that can enhance legal certainty within Indonesia’s dual legal framework. Keywords: maslahah; legal certainty; divorce administration; family law; Indonesian law.